Optimisation of the Conversion and Extraction of Arctigenin From Fructus arctii Into Arctiin Using Fungi - Lu, Zheng; He, Bin; Chen, Jie; Wu, Li-Jun; Chen, Xia-Bing; Ye, Sheng-Qiang; Yang, Wen-Hai; Shao, Zhi-Yong; Jin, Er-Guang; Wang, Si-Jiu; Zhou, Hong-Bo; Cao, Ji-Yue (Frontiers in Microbiology, 2021)
Fructus arctii is commonly used in Chinese medicine, and arctiin and arctigenin are its main active ingredients. Arctiin has low bioavailability in the human body and needs to be converted into arctigenin by intestinal microbes before it can be absorbed into the blood. Arctigenin has antiviral, anti-inflammatory, and anti-tumour effects and its development has important value. In this study, we used external microbial fermentation with Aspergillus awamori and Trichoderma reesei to process and convert arctiin from Fructus arctii powder into arctigenin, hence increasing its bioavailability. We developed a fermentation process by optimising the carbon and nitrogen source/ratio, fermentation time, pH, liquid volume, inoculation volume, and substrate solid-liquid ratio. This allowed for an arctiin conversion rate of 99.84%, and the dissolution rate of the final product was 95.74%, with a loss rate as low as 4.26%. After the fermentation of Fructus arctii powder, the average yield of arctigenin is 19.51 mg/g. Crude fermented Fructus arctii extract was purified by silica gel column chromatography, and we observed an arctigenin purity of 99.33%. Our technique effectively converts arctiin and extracts arctigenin from Fructus arctii and provides a solid basis for further development and industrialisation.